Pendampingan Perancangan Chatbot Sebagai Media Interaktif Dalam Menghadapi Tantangan Era Digitalisasi - Ardiansyah Ardiansyah (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
The implementation of this Community Service (PKM) activity is assisting in the design or manufacture of chatbots which is a series of training activities for making chatbots. This PKM is a national activity whose participants come from various districts/cities in Indonesia. The urgency of this PKM for participants is: (a) For teachers and lecturers because the development of educational technology is a necessity in the current digitalization era; (b) For the general public, because the chatbot working mechanism is the primary factor to be applied in various professional fields, chatbots are not only applied to educational institutions but also in business activities. In particular, for participants through this PKM, the aim is for participants to be able to design a chatbot application and can use it according to the instructions given to the system through the Smojo.Ai platform. This PKM method is carried out online using video conference zoom cloud meetings, Google meet, and WhatsAps Group (WAG) which consists of 3 (three) stages starting from the preparation stage to the evaluation stage from September to October 2022. The achievements of this PKM of 90% which is the average value of the tests carried out, namely: (a) Based on the results of the participant chatbot design, the predetermined target is 80%; (b) Based on the results of testing the participant's chatbot accuracy shows a result of 100%. The implication of the results of this PKM is to contribute to literacy and skills for participants in keeping up with the times, especially information technology which currently influences most activities in the education and business sectors. The next stage of development after the PKM has been successfully carried out is that participants are expected to be able to develop their skills to create and design chatbots independently according to their needs, profession, and field of work which can not only be applied to the education sector but can also be applied to various sectors. Chatbots can be developed in the tourism, retail, service, and other sectors that require customer service to answer repeated questions or for other needs.